(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The extracurricular sports program at SMP Negeri 10 Kota Jambi has not shown optimal results. Based on this problem, the researcher decided to conduct a study on the basic skills of playing futsal. The purpose of this study was to determine the basic technical skills of playing futsal among the boys’ futsal team at SMP Negeri 10 Kota Jambi. This study was descriptive in nature and used a survey method. The population in this study was all 20 students on the boys’ futsal team at SMP Negeri 10 Kota Jambi. The instrument used was a futsal skills test. To determine the level of futsal skills, three test items were used, namely: 1) Short Pass 2) dribbling, 3) shooting. The results of the study showed that the basic futsal skill level of students on the boys’ futsal team at SMP Negeri 10 Kota Jambi who participated in the mayor’s cup was categorized as very good (10% or 2 students), good (15% or 3 students), 80% in the adequate category with a total of 8 students, 30% in the poor category with a total of 6 students, and 5% in the very poor category with a total of 1 student.